Using Literature Based Discovery to Gain Insights Into the Metabolomic Processes of Cardiac Arrest - Henry, Sam; Wijesinghe, D. Shanaka; Myers, Aidan; McInnes, Bridget T. (Frontiers in Research Metrics and Analytics, 2021)
In this paper, we describe how we applied LBD techniques to discover lecithin cholesterol acyltransferase (LCAT) as a druggable target for cardiac arrest. We fully describe our process which includes the use of high-throughput metabolomic analysis to identify metabolites significantly related to cardiac arrest, and how we used LBD to gain insights into how these metabolites relate to cardiac arrest. These insights lead to our proposal (for the first time) of LCAT as a druggable target; the effects of which are supported by in-vivo studies which were brought forth by this work. Metabolites are the end product of many biochemical pathways within the human body. Observed changes in metabolite levels are indicative of changes in these pathways, and provide valuable insights towards the cause, progression, and treatment of diseases. Following cardiac arrest, we observed changes in metabolite levels pre- and post-resuscitation. We used LBD to help discover diseases implicitly linked via these metabolites of interest. Results of LBD indicated a strong link between Fish Eye Disease and cardiac arrest. Since fish eye disease is characterized by an LCAT deficiency, it began an investigation into the effects of LCAT and cardiac arrest survival. In the investigation, we found that decreased LCAT activity may increase cardiac arrest survival rates by increasing omega-3 polyunsaturated fatty acid availability in circulation. We verified the effects of omega-3 polyunsaturated fatty acids on increasing survival rate following cardiac arrest via in-vivo with rat models.